Reformas curriculares no curso de formação de oficiais aviadores na Academia da Força Aérea entre 1974 e 2014 - Zibordi, Paulina Montejano (Universidade Federal de São Carlos, 2015)
This study falls into the history, philosophy and education sociology research line and its aim is to analyze the graduation of aviator officers at the Brazilian Air Force Academy. Our goal has been to reach an understanding of changes in the course curriculum, considering historical factors as well as the need for such changes. Our research starts in 1974, when the Air Force Academy was transferred to the country town of Pirassununga, up to the present time. Our bibliographical research suggests that the several curriculum modifications were not based on previous study and were not closely related to the doctrine and military strategy either. We have concluded that Brazil's political and economical situation, combined with a post-cold-war military identity crisis, turned military education into a bureaucratic activity and that has considerably compromised the profile of Brazil's war leaders. So we have analyzed the proposals for curriculum changes in the Aviator Officers Course in order to find how such changes were carried out and, most importantly, to find if they are compatible with the new standards of aviator's graduation and the new managerial tasks required. For that research our primary sources have been the Aeronautical Documentaion Center, the Air Force Academy archives and the legislation. We have also interviewed lieutenants who graduated in 2009 in order to hear their opininions on the adequacy of the new curriculum to the daily routine of an aviator.
Keywords: Educação - história; Formação de oficiais; Ensino superior; Educação militar; Reforma do ensino; Currículos; Military high education; Curriculum modifications; CIENCIAS HUMANAS::EDUCACAO